A quantitative study of the actions of excitatory amino acids and antagonists in rat hippocampal slices. - Blake, J. F. (1988)
1. A quantitative pharmacological investigation of the actions of excitatory amino acids on hippocampal CA1 neurones has been made using a new slice preparation developed for grease gap recording; d.c. potential was measured across a grease barrier placed between alvear fibres and the bathing medium. 2. In Mg2+-free perfusate, N-methyl-D-aspartate (NMDA, 1-100 microM), quisqualate (1-500 microM), kainate (1-200 microM) and alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA, 1-100 microM) caused dose-dependent depolarizations. 3. The dose-response relationships were fitted to logistic expressions. The maximum responses to AMPA, NMDA and kainate were similar; their respective EC50 values were 5, 13 and 23 microM. Quisqualate had a smaller maximum; its EC50 value was 10 microM. The slopes of the dose-response relationships were different for the 4 agonists; the order of steepness of the slopes was NMDA greater than AMPA greater than kainate greater than quisqualate. 4. Similar amino acid-induced depolarizations were observed in slices of just the CA1 region or in whole slices bathed in tetrodotoxin. Isolated alvear fibres, however, were insensitive to the excitatory amino acids. 5. D-2-Amino-5-phosphonovalerate (APV, 50 microM) selectively and reversibly antagonized responses induced by NMDA (apparent pA2 = 5.21). 6. Kynurenic acid (1 mM) reversibly depressed responses to the three agonists tested. The dose-ratios for antagonism of AMPA, kainate and quisqualate were 6.9, 5.6 and 4.6 respectively. 7. This preparation has a different sensitivity profile to agonists from those of previously reported preparations of spinal cord, neocortex and cerebellum.(ABSTRACT TRUNCATED AT 250 WORDS)